MODELING THE OPERATION OF A GALVANIC BATH WITH ELECTRIC HEATERS AND OPTIMIZING ITS DESIGN BASED ON NUMERICAL SIMULATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
A model of the processes in a galvanic bath during heating is based on the finite element method. The processes of heating the air chamber and directly the reagent solution are simulated. Based on the constructed model, an automatic control system for heating elements is being developed, which provides a sufficient heating rate, a stable temperature and protects the heating elements from burnout. An application program has been created that allows performing the calculations without studying complex modeling systems.